Policy experiment in Mozambique highlights importance of gender in dissemination of sustainable land management techniques - Kondylis, Florence; Mueller, Valerie; Sheriff, Glenn; Zhu, Siyao Jessica (International Food Policy Research Institute, 2014)
One potential path for increasing yields is to invest in land cultivated by women. Although agricultural intensification has been the standard approach to increase yields, there is a recent push to emphasize sustainable land management (SLM). The traditional mode of technology diffusion is through the provision of agricultural extension services, which typically cater to male farmers. To better understand the role of gender in the dissemination of SLM techniques, we exploit a policy experiment conducted in 200 communities in the Zambezi valley of Mozambique.